THE VALIDITY MULTIMEDIA INTERACTIVE BASES ANDROID ON IONIC BOND MATERIAL - Muhammad Kharis Syarifuddin; Kusumawati Dwiningsih (Universitas Negeri Surabaya, 2020)
This research is aims to describe the validity of interactive multimedia based on Android in the ion bonding sub material. This research uses Thiagarajan's 4-D development research consisting of Define; Design; Development and Disseminate. However, this research is limited to the Development stage of Thiagarajan in Ibrahim (2014). Multimedia validity is reviewed from the aspect of content validity and construct validity. This multimedia was validated by 2 Unesa chemistry lecturers and 1 chemistry teacher with the research instrument used in the form of a multimedia validation sheet then the results of the validation resulted in a validation score. Based on data analysis, it can be concluded that android-based interactive multimedia on the ion bond sub-material is valid for use with percentage content validation and construct validity respectively 91.85% and 89.61% with highly valid criteria.